Gastroduodenal Ulcer in High Altitude (Peruvian Andes) - Garrido Klinge, Germán (1960)
Peptic ulcer is one of the most common diseases, but, despite all the research done trying to discover its pathogenic mechanism, there is nothing definite yet. According to the data reported in the literature (7) concluded that up to 10% of the adult male population suffering from ulcer at any point in their life. It attacks mainly the sector of the population that develops most productive activity, so the economic impact is enormous. Because of this is that any new aspect of this disease that is studied is important, since all gathered results may someday lead to solving the problem of exciting gastroduodenal ulcer.